Feline mammary tumours in western Canada. A retrospective study - Abdul Rahman, Sheikh Omar (Veterinary Association Malaysia, 1980)
A retrospective study of all cases of mammary tumours in the cat covering a ten-year period was made from the files of the department of Veterinary Pathology, University of Saskatchewan, Saskatoon. Forty-tour cases were seen from a total of 3,441 feline accessions. The mean age of the affected cats was 10.5 years with over 90% found in cats 8, years or older. The domestics end the Siamese were the major breeds effected. Carcinomas represented 82% of the tumour and half of the benign tumours were mammary gland hypertrophy.